Feasibility study on handheld devices-based augmented reality system for identification and inspection processes in manufacturing industry / Chiang Yoong Fatt - Chiang, Yoong Fatt (2019)
The use of Augmented Reality (AR) in assisting inspectors during an identification and inspection tasks can be considered a practical and innovative method to reduce human error in reading mechanical drawing and improve productivity. This research project carries out a feasibility study of the implementation of handheld devices-based AR system in the manufacturing context, to support inspectors in carrying out quality inspection tasks. A feasibility study and its application to quality inspection has been carried on in collaboration with a Malaysia-based manufacturer of automated equipment. This case study targeted to a low-volume, high variation manufacturing company that is experiencing issues reducing its defects in incoming fabricated parts. Defects happened on fabricated parts such as missing important under-cut feature or engraving text. A prototype handheld device-based AR system is intended to be applied as effective tools to help inspector perform inspection tasks by viewing 3D model compared with the fabricated part. The expected pros or cons of its implementation and acceptance are discussed.